Intervensi Ergonomi untuk Menurunkan Beban Kerja pada Operator Lantai Produksi Bisnis Unit South Copper Rod - Kevin Salsia; Dian Mardi Safitri; Ranny Dwi Anggraini (JURNAL TEKNIK INDUSTRI, 2018)
Workload is a set or number of work activities that must be completed by an organizational unit. Activities carried out by humans will cause physical fatigue and psychological (mental) fatigue. Workload measurement is used to refine the size of the workload experienced by someone in carrying out activities, and to increase the level of productivity in work. This study aims to reduce the workload on the production floor. Based on research conducted by interviews and (surveys) found symptoms of excessive workload. The workload found is in the form of work stress and fatigue due to excessive physical activity. Measurement of mental workload using the NASA-TLX method and measurement of physical workload using the cardiovascular load method. The stages of the study were continued by finding the correlation between workload and reaction time. The results of the correlation of physical workload get a value of 0.334 which means "sufficient correlation" while the results of mental workload with reaction time get a value of 0.141 which means "very weak correlation". Based on the correlation results, the physical workload was chosen for ergonomic intervention because the coefficient of physical workload was higher than the mental workload. The proposed improvements provided were in the form of working time arrangements of 54.81 minutes and rest periods of 13.12 minutes for 20 production floor operators and carried out for 30 working days. The results of the next improvement proposal will be implemented to the company with% CVL before implementation of 33.75% with the category "needed improvement" and after implementation with% CVL of 27.1% with the category "no fatigue occurs"